Biosynthesis of gold nanoparticles (AuNPs) by Diopatra claparedii grube, 1878 (Polychaeta: Onuphidae) and its antibacterial activity - Piong, Chong Huai; Noor Aniza Harun,; Ung, Angeline Ee Pei; Mohammad Asyraf Adhwa Masimen,; Wan Iryani Wan Ismail,; Izwandy Idris, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Gold nanoparticles (AuNPs) have gained attention as it possesses outstanding physicochemical properties, and utilised in variety of applications especially in biomedical and pharmaceutical. Majorly, AuNPs are produced by conventional methods (chemical and physical). However, these methods bring several drawbacks such as toxic, hazardous, low yield and non-environmental friendly. Hence, biosynthesis of AuNPs that compliance with ‘greener’ approach becomes vitals. In this study, marine tube worm of Diopatra claparedii (polychaetes) was employed as reducing agent in the biosynthesis of AuNPs. The biosynthesised of AuNPs by D. claparedii extract was successfully prepared under ambient temperature and normal atmospheric conditions. The formation of AuNPs was confirmed by the appearance of surface Plasmon resonance (SPR) bands around 540 to 560 nm characterized by UV-Vis spectroscopy. Scanning electron microscopy (SEM) showed that the AuNPs are mostly in agglomerated spherical like shapes with size ranging from 100 to 400 nm. Meanwhile, transmission electron microscopy (TEM) showed that the particles are in the size range from 25 to 60 nm, also mainly form in spherical like shape. The particle size of AuNPs in a range of 50-100 nm was showed by dynamic light scattering (DLS). Fourier-transform infrared (FTIR) spectrum of D. claparedii extract indicated the existence of several functional groups. Biosynthesised AuNPs also successfully gave inhibition on bacterial growth (Staphyloccus aureus, S. epidermidis, Escheratia coli, Salmonella typhi) through antibacterial assessment.